Responsabilidade civil pré-contratual e pós-contratual no direito do trabalho - Scaquetti, Sonia Cristina (2015)
The purpose of this study is mainly, but not limited to, the analysis of how Labor Law and Civil Law have been brought closer, starting from the Federal Constitution of 1988 and the Civil Code of 2002, which affected profoundly contemporary private relations, which explains why it has been called Constitutionized Civil Code. The process of bringing closer Labor Law and Civil Law is considered a return trip to the origins of Labor Law, within Civil Law. This approach has been treated as the solution to labor relations disputes and the ultimate valorization of the workers dignity. As a consequence, the study intends to validate the applicaton of the Civil Code within Labor Law, aiming conflict resolution, and to conclude whether or not there is compatibility in the application of the principles of objective good faith, equity and the social function of contract, those which became Law as part of article 422 of the 2002 Civil Code. Therefore as we transfer Civil Code concepts to the concrete cases within Labor Law, far more reaching decisions can be made and we depart from mere individual rights to the civil responsibility of contracts. By doing this, workers will benefit from a legal protection unheard of or even imagined before